Strengthening pharmacy practice: development and validation of the Resilience Scale - Jocić, Dragana (Vojnosanitetski pregled, 2024)
Background/Aim. Despite the demanding nature of their roles in community pharmacies and their critical importance to patient safety, healthcare professionals, including pharmacists, are often not covered by the Resilience Scale. Therefore, the aim of the study was to develop and validate a resilience scale specifically tailored for pharmacists working in community pharmacies. Methods. The study involved the development and validation of a scale aimed at assessing psychological resilience among community pharmacists. The domains and items of the scale were considered from the aspect of reviewing the available literature. Content validation by subject matter experts and subsequent computation of the content validity index ensured the scale’s content validity. Face validity assessment ensured alignment with the intended construct. The final scale was distributed to a sample of 504 community pharmacists, after which the scale was analyzed using statistical methods such as factor analysis, multiple regression, and reliability analysis.  Additionally, test-retest reliability analysis was performed on 80 community pharmacists. Results. During the brainstorming sessions and focus groups, 95 items were generated within five domains – Confidence, Agility, Coping with stress, Interpersonal relations, and Developmental thinking. Following expert review and rigorous content and face validity analyses, 30 items with Content Validity Index and Face Validity Index values surpassing 0.80 were retained. The scale exhibited strong internal consistency, with Cronbach’s alpha exceeding 0.9. Factor analysis confirmed the five-factor structure, with each component displaying high factor loadings and significant variable loadings on only one component. Conclusion. The Resilience Scale emerged as a promising tool for assessing community pharmacists’ resilience, demonstrating robust psychometric properties. The study contributed validity evidence concerning content and internal structure, thereby enhancing the scale’s credibility in evaluating resilience domains within the pharmacy profession.
Keywords: data interpretation, statistical; pharmacists; resilience, psychological; serbia; surveys and questionnaires